Commissioner Size and Return on Asset: Efficiency as A Moderator - Simbolon, Ramadona; Elviani, Sri (PT. Riset Press International, 2026)
The objective of this study is to investigate the impact of the number of commissioners (UDK) and independent commissioners (KOMID) on Return on Assets (ROA), and empirically examine the role of the Operating Expense to Operating Revenue (BOPO) ratio as a moderator variable. The population of this research is state-owned companies (BUMN) that have established a holding. The sampling process was conducted using the purposive sampling technique, in which selected SOEs that had been operating for at least one year since the holding company’s establishment were selected, resulting in a sample of 52 firms. Data were analyzed using the Moderated Regression Analysis (MRA) technique with interaction testing. Findings of the present study confirm that BOPO serves as a moderating variable in the relationship between commissioner governance and Return on Asset (ROA), although there is no statistically significant direct relationship between UDK, KOMID, and BOPO and ROA. However, this study seeks to address limitations in corporate governance research by using BOPO as a moderator variable. The emphasis on BUMN Holding firms is also a useful contribution, given that very few empirical studies have specifically addressed these strategic companies in the context of governance and operating performance. SOE governance reform is underscored both by a greater number of independent commissioners and by substantially enhanced roles. Structural reform must be followed by the refinement of processes, organizational culture, and genuine accountability in decision-making to achieve increasingly sustainable financial performance in the BUMN sector.